Nurses’ qualifications to order and prescribe medications – expectations versus reality - Lesiak, Aneta; Marć, Małgorzata S.; Zdziebło, Kazimiera; Rękas, Magdalena; Krakowiak, Anna; Martyn, Julia (Nursing Problems / Problemy Pielęgniarstwa, 2018)
From 1st January 2016 nurses and midwives, proportionally to their qualifications are eligible to order and prescribe medications self-dependently; they are also eligible to continue writing medications in accordance with doctors’ recommendations. They can also refer patients to medical examinations. It is an important step, which should improve functioning of healthcare system, facilitate patients’ access to healthcare services and strengthen the status of nurses and midwives. The aim of this paper is to show the scope of qualifications to write prescriptions in comparison to a degree such qualifications are exercised by the nurses of the Świętokrzyskie region. The object of the analysis is the extent and character of nurses’ competencies to order medications and write prescriptions and their practical usage. The range of data includes number of nurses writing prescriptions as well as the number of prescriptions written by nurses and filled in around Świętokrzyskie region between 2016 and the first 6 months of 2018.